Translanguaging as a Counter-Narrative in EFL Practice - Setiono Sugiharto (Universitas Islam Negeri (UIN) Mataram, 2023)
While concerns over inequalities of multilingualism – a real phenomenon in multilingual countries due to the positive attitudes toward English as a global language – should not be overlooked, there are occasions especially in a classroom context where multilingual speakers defy the exclusive use of English, and instead creatively mix the English language with their own mother tongues, resulting in translingual Englishes (Dovchin, Sultana & Pennycook, 2016). In this paper, I will show that despite the strict imposition of the English-only-policy in schools in Indonesia – a source of inequalities in learning and teaching in the country – both students and teachers manage to surreptitiously translanguage their interactions using varied linguistic codes for achieving successful communication in a class interaction. I see their translingual Englishes as a strategic practice initiated by the teachers to not only open up a space for them to reveal their real multilingual identities, but also to legitimize these identities. Finally, in teacher-dominated classrooms where students often keep silent and are unwilling to initiate a conversation and to argue over a controversial issue, translanguaging is a pedagogically useful practice for encouraging students to negotiate tensions that might occur in their effort to grapple with their learning of English. Thus, a focus on the ‘unequal’ in the classroom also leads to uncovering translingual spaces where efficient teaching and learning are facilitated, and multilingual identities affirmed.